Parameter Calculation and Experimental Research of LCL-filter of Photovoltaic Grid-connected Inverter - LIU Zhaoyi; LI Shaolong; ZHAO Xianggui; ZHANG Honghao (Kongzhi Yu Xinxi Jishu)
LCL-filter is the essential part of photovoltaic grid-connected inverter. With the actual parameters, the numerical value of filter inductance of inverter side and the ratio between the filter inductance of grid side and filter capacitance were calculated in detail. The relationship between various inductances’ ratio and resonance frequency was researched. By means of Bode-plot and Matlab/simulink, appropriate values of inductance and capacitance were obtained to get the best harmonic suppression. Finally, the results of theoretical analysis were verified by the practical experiment data.